Exploring criminal justice policy transfer models and mobilities using a case study of violence reduction - Graham, William (Criminology & criminal justice, 2022)
Although there is growing interest in criminal justice policy transfer, a dearth of empirical research in this area has been acknowledged. This article addresses this gap by presenting the results of research conducted on a case of policy transfer of a criminal justice programme, focused on group/gang violence reduction, from America to Scotland. Policy transfer models were used to develop, frame and conduct the analysis of what was considered a ‘successful’ programme transfer; however, it was found that no single model could fully account conceptually for a key finding of the research, namely a policy transfer ‘backflow’. This article details the key processes, mechanisms and outcomes of the policy transfer and in doing so reflects on the usefulness of orthodox and non-orthodox/social-constructionist policy transfer approaches in understanding the outcomes of this case of criminal justice programme transfer.